Pseudo-hermafroditismo masculino em um equino - Bueno, Verônica La Cruz; Nogueira, Carlos Eduardo Wayne; dos Santos, Bianca Lemos; Coelho, Ana Carolina Barreto; Oliveira, Douglas Pacheco; Bobrowski, Vera Lucia; Martino-Roth, Maria da Graça; Curcio, Bruna da Rosa (Acta Scientiae Veterinariae, 2017)
Background: Intersexuality is considered an alteration in the animal development that opposes the characteristics determined by the genetic sex, resulting in an individual with characteristic features of both sexes. The objective of this work is to report a case of male pseudohermaphroditism of a Criollo breed horse referred to the Hospital de Clínicas Veterinárias (HCV) of the Universidade Federal de Pelotas, RS, Brazil. We gather information on the intersexuality diagnostics highlighting cytogenetics as an additional tool to diagnosis. Case: A Criollo breed horse was attended at the HCV with the main complaint of morphological anomaly of the external genitalia. The animal presented female external features, characterized by mammal glands and female genitalia. The horse also showed a rudimentary penis-like structure, caudally oriented shrouded by a cutaneous crease similar to a vulva and presented male behavior. The external genitalia was examined but the vaginoscope could not be inserted since the crease ended in a sac, with no openings. Rectal palpation and transrectal ultrasound could not reveal the presence of female gonads. Urethral ultrasound revealed the pelvic urethra and the openings of the male accessory glands. The equine was subjected to hormonal challenge with human chorionic gonadotropin (hCG). First sample presented a testosterone concentration of 20 ng/dL; second sample, on the other hand, presented a testosterone concentration of 60 ng/dL after the stimulus. The Polimerase Chain Reaction technique revealed absence of gene SRY (sex determiningregion Y). The cytogenetic study was conducted with the lymphocytes obtained from peripherical venous blood. From this, we could verify that the patient was genetically male with karyotype 64 XY. Necropsy showed presence of prepuce and rudimentary penis at the anatomical site of the vulva without scrotum. In the pelvic cavity, a structure similar to a uterine body was observed, with the horns ending at the ovaries anatomical sites, where a structure similar to testicles was found with underdeveloped seminiferous tubules lacking production of spermatozoa and rudimentary epididymis with epididymal ducts coated with primitive stereocilia. Discussion: True hermaphroditism is defined by the presence of ovarian and testicular tissues in the same individual, as separate gonads or combined, as ovotestis. On the other hand, the pseudo-hermaphrodite is an individual with only one gonad, and external genitalia and secondary characteristics of the opposite sex. Urethral endoscopy allowed the visualization of the pelvic urethra and the male sexual glands openings. Following stimulation with hCG, testosterone level increased in 40 ng/dL, evidencing the presence of testicular tissue. Sexual differentiation is determined by the presence or absence of the Y chromosome and by the expression of gene SRY. The animal studied here had karyotype 64 XY and lacked gene SRY, characterizing a condition where testicular differentiation occurred in the absence of gene SRY. It is possible to conclude that clinical evaluation, complementary exams and hormonal analysis allowed the identification of intersexuality. However, only molecular, cytogenetic and histological analyses allowed the definitive diagnosis of male pseudohermaphrodite.